2016
DOI: 10.1038/mt.2016.24
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 Can Inhibit HIV-1 Replication but NHEJ Repair Facilitates Virus Escape

Abstract: Several recent studies demonstrated that the clustered regularly interspaced short palindromic repeats (CRISPR)-associated endonuclease Cas9 can be used for guide RNA (gRNA)-directed, sequence-specific cleavage of HIV proviral DNA in infected cells. We here demonstrate profound inhibition of HIV-1 replication by harnessing T cells with Cas9 and antiviral gRNAs. However, the virus rapidly and consistently escaped from this inhibition. Sequencing of the HIV-1 escape variants revealed nucleotide insertions, delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
236
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(264 citation statements)
references
References 27 publications
16
236
1
Order By: Relevance
“…However, if only single gRNA is used for a single target site, it is possible to generate InDels where the mutated gene can be changed in such a way as to allow the virus to replicate but yet no longer be susceptible to cleavage by Cas9 because its mutated sequence is now different to the Cas9/gRNA target sequence, i.e., an “escape mutant”. (Wang et al, 2016a, 2016e; Khalili et al, 2017). Thus when designing any gene editing strategy against HIV, it is essential to consider the possibility of escape mutants arising (White et al, 2016).…”
Section: Recent Applications Of Crisprmentioning
confidence: 99%
“…However, if only single gRNA is used for a single target site, it is possible to generate InDels where the mutated gene can be changed in such a way as to allow the virus to replicate but yet no longer be susceptible to cleavage by Cas9 because its mutated sequence is now different to the Cas9/gRNA target sequence, i.e., an “escape mutant”. (Wang et al, 2016a, 2016e; Khalili et al, 2017). Thus when designing any gene editing strategy against HIV, it is essential to consider the possibility of escape mutants arising (White et al, 2016).…”
Section: Recent Applications Of Crisprmentioning
confidence: 99%
“…Indeed, one study identified a mutational insertion in a highly conserved region of pol that provided resistance to subsequent endonuclease cleavage but did not lethally mutate the virus [69]. In another study, virus escaped CRISPR/Cas9 targeting of several conserved regions of the HIV genome [70]. These results highlight the need for careful choice of target and suggest that simultaneous targeting of multiple essential genes may be necessary.…”
Section: Targeting the Hiv Genome Directlymentioning
confidence: 99%
“…25 Similar resistance mutants have been shown to emerge and replicate in cultures undergoing treatment with HIV-targeted Cas9. [26][27][28] Fortunately, it appears that the emergence of resistance can be successfully managed in a manner that is analogous to traditional antiviral therapy, by simultaneously targeting multiple sites within the viral genome. Although ten or more sites may be required if targeting is limited to the LTR, 22 attacking other more conserved sites elsewhere in the genome may allow fewer targets to suffice.…”
Section: Resistancementioning
confidence: 99%